METIONINA MAIS CISTINA DIGESTIVEL EM RAÇÕES PARA ALEVINOS DE TAMBATINGA. - COSTA, Dayana da Conceição da (2020)
Two simultaneous experiments lasting 50 days were carried out. In the first experiment, the objective was to determine the digestible methionine plus cystine to lysine ratio in rations for tambatinga fingerlings. In the second experiment, the objective was to determine the digestible methionine plus cystine requirements in rations for tambatinga fingerlings. In each experiment, 900 tambatinga fingerlings with an average initial weight of 1.49 ± 0.59 to 4.14 ± 1.73 were used in a randomized block design, with six repetitions in time per treatment (three repetitions in two blocks) and 25 fish per experimental unit. In the first experiment, the treatments consisted of six isolisinic rations (1.45%) containing different digestible methionine plus cystine: lysine ratios (50, 55, 60, 65, 70 and 75%), formulated by the amino acid supplementation technique. In the second experiment, the treatments consisted of six diets containing different levels of digestible methionine plus cystine (0.60; 0.75; 0.90; 1.05; 1.20 and 1.35%), formulated by the dilution technique. The methionine plus cystine to lysine ratio was estimated using the 1.80% level of digestible lysine. In each experiment, performance, feed efficiency, body composition and nitrogen retention efficiency parameters were evaluated. In the first experiment, the elevation of the digestible methionine plus cystine: lysine ratio increased quadratically feed intake, digestible methionine plus cystine intake, weight gain, specific growth rate, body deposition of protein and ash, and nitrogen retention efficiency of fishes, up to the ratios of 57%, 73%, 58%, 58%, 59%, 58% and 60%, respectively. The feed: gain ratio improved in a quadratic way until the estimated ratio of 59% of digestible methionine plus cystine: lysine. The efficiency of using methionine plus cystine for the weight gain of fishes decreased linearly. The body deposition of fat was not influenced by the treatments. It was concluded that the digestible methionine plus cystine: lysine ratio is 59%, based on the body deposition of protein. In the second experiment, the increase in methionine plus cystine levels reduced quadratically feed intake and increased weight gain and specific growth rate, improved the feed: gain ratio, and increased body deposition of protein and ash until to estimated digestible methionine plus cystine levels of 0.89%; 1.11%; 1.14%, 1.01%, 1.07% and 1.02%, respectively. The efficiency of using mythionine plus cystine for weight gain and body deposition of fat decreased linearly with the increase in the dietary concentration of sulfur amino acids. The nitrogen retention efficiency reduced in a quadratic way until the estimated digestible methionine plus cystine level of 0.65%. It was concluded that the dietary requirement of digestible methionine plus cystine total and digestible for tambatinga fingerlings is 1.15% and 1.07%, respectively, corresponding to the digestible methionine plus cystine to lysine ratio of 59%.